PENERAPAN MODEL PEMBELAJARAN BERMAIN DAN MUSIK UNTUK MENINGKATKAN HASIL BELAJAR PAI PESERTA DIDIK SMP BP AL MUNAWWAROH MERAUKE - SRI WAHYUNINGSIH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
This study aims to improve the learning outcomes of the PAI Budi Pekerti subject on commendable morals for class IIA SMP Al Munawwaroh Merauke Islamic Boarding School in the 2022/2023 academic year, by applying the learning model